Testing Tuberculosis Drug Efficacy in a Zebrafish High-Throughput Translational Medicine Screen - Ordas, Anita (Antimicrob Agents Chemother, 2015)
The translational value of zebrafish high-throughput screens can be improved when more knowledge is available on uptake characteristics of potential drugs. We investigated reference antibiotics and 15 preclinical compounds in a translational zebrafish-rodent screening system for tuberculosis. As a major advance, we have developed a new tool for testing drug uptake in the zebrafish model. This is important, because despite the many applications of assessing drug efficacy in zebrafish research, the current methods for measuring uptake using mass spectrometry do not take into account the possible adherence of drugs to the larval surface. Our approach combines nanoliter sampling from the yolk using a microneedle, followed by mass spectrometric analysis. To date, no single physicochemical property has been identified to accurately predict compound uptake; our method offers a great possibility to monitor how any novel compound behaves within the system. We have correlated the uptake data with high-throughput drug-screening data from Mycobacterium marinum-infected zebrafish larvae. As a result, we present an improved zebrafish larva drug-screening platform which offers new insights into drug efficacy and identifies potential false negatives and drugs that are effective in zebrafish and rodents. We demonstrate that this improved zebrafish drug-screening platform can complement conventional models of in vivo Mycobacterium tuberculosis-infected rodent assays. The detailed comparison of two vertebrate systems, fish and rodent, may give more predictive value for efficacy of drugs in humans.